Enhancing decision-making skills through geoscience education for sustainable development - Eko Hariyono; Madlazim Madlazim; Hasan Nuurul Hidaayatullaah; Tomonori Ichinose (Institute of Advanced Engineering and Science, 2024)
Sustainable development (SD) can be achieved through education. The goal of incorporating SD principles into education is to enhance both the present and future quality of human life. This study analyzes learning effectiveness by developing education for sustainable development (ESD) based inquiry to improve students’ decision-making skills. Specifically, this study aimed to explore ESD-based inquiry learning tools, analyze student decision-making skills, and analyze student responses to ESD-based inquiry learning tools. The development research used is a 4D model (define, design, develop, and disseminate) and a one-group pre-test-posttest design. Validation sheets, tests, and questionnaires are employed as data-gathering tools. Data analysis using percentage, mean, n-gain, and paired sample t-test techniques. The results showed the following: i) ESD-based inquiry learning tools developed according to the assessment of experts and practitioners are in the valid and reliable category in terms of both construction and substance; ii) the ESD-based inquiry learning is effective in improving students’ decision-making skills with an average gain (gain score) in the high category; and iii) the student's response to each learning process using ESD-based inquiry learning is very good and is considered more exciting and motivating. This finding contributes to educators developing various ESD-based learning materials, especially geoscience materials, to achieve quality learning.